RANCANG BANGUN SEDERHANA SISTEM REVERSE OSMOSIS (RO) UNTUK MENINGKATKAN pH AIR UNIT LISTRIK DI BANDAR UDARA CAKRABHUWANA CIREBON - Haryadi Wibowo, Imam; Samudera N.A.N, Muhammad; Putri , Sasqia; Sanjaya, Diki; Panca, Alvian; Sholeh, Ikmal (Program Studi Teknik Mekanikal Bandar Udara, 2024)
Cakrabhuwana Airport Cirebon is a Technical Implementation Unit (UPT) formed based on the Decree of the Minister of Transportation of the Republic of Indonesia number KM 166 of 2019 concerning the National Airport Order which has the task of serving civil aviation. Cakrabhuwana Airport has a source of clean water that comes from the ground / well, besides that Cakrabhuwana Airport also uses PDAM water as a clean water supply which is only distributed specifically to the terminal. Water from wells / soil is used to support flight activities, but the water obtained from the well / soil is not optimal because the color of the water is still found yellow and not clear. After measuring the PH of water in each airport unit, it was found that the condition of the water in the electricity unit was still below the normal standard of clean water. To overcome this problem, the authors designed a simple reverse osmosis device in the form of a prototype that is used to convert the pH of substandard water into normal PH of clean water